Dynamic moduli of magneto-sensitive elastomers: a coarse-grained network model. Issue 38 (14th October 2015) - Ivaneyko, Dmytro; Toshchevikov, Vladimir; Saphiannikova, Marina
<x xml:space="preserve">Abstract</x> The viscoelastic properties of magneto-sensitive elastomers (MSEs) in a low-frequency regime are studied using a coarse-grained network model.